Vestibular Testing. Issue 2 (April 2021) - Hain, Timothy C.; Cherchi, Marcello
ABSTRACT: PURPOSE OF REVIEW: Vestibular testing, both at the bedside and in the laboratory, is often critical in diagnosing patients with symptoms of vertigo, dizziness, unsteadiness, and oscillopsia. This article introduces readers to core concepts, as well as recent advances, in bedside and instrumented vestibular assessments. RECENT FINDINGS: Vestibular testing has improved immensely in the past 2 decades. While history and bedside testing is still the primary method of differential diagnosis in patients with dizziness, advances in technology such as the ocular vestibular-evoked myogenic potential test for superior canal dehiscence and the video head impulse test for vestibular neuritis have capabilities that go far beyond the bedside examination. Current vestibular testing now allows clinicians to test all five vestibular sensors in the inner ear. SUMMARY: Contemporary vestibular testing technology can now assess the entire vestibular periphery. Relatively subtle conditions, such as superior canal dehiscence or a subtle vestibular neuritis, can now be diagnosed with far greater certainty.